Development of the Competency Model of Graduate Student of the Supplementary Programs in the Field Public Procurement - Olga Aleksandrovna Shabanova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with the process of generation and development of the competency model of graduate student of the supplementary programs in the field public procurement. Based on the competency approach review and public procurement laws analysis the author substantiates recommendations for the formation of the competency model in modern Russian conditions.